INVESTIGATING STUDENTS' ANXIETY IN ARGUMENTATIVE WRITING - Saputra, Andika Guruh (Universitas Mahaputra Muhammad Yamin, 2023)
This study investigated the anxiety-related challenges faced by students in argumentative writing and their impact on writing performance. The research utilized questionnaires to collect quantitative data from fourth-semester students enrolled in the Argumentative Writing Subject. The study explored psychological, emotional, and cognitive obstacles that impede students' writing abilities and contribute to anxiety. Results indicated that 31.8 percent of students reported psychological symptoms such as excessive sweating and trembling hands when engaging in argumentative writing tasks. These manifestations highlighted the negative influence of anxiety on learning outcomes, emphasizing the need for support and interventions. By addressing psychological, emotional, and cognitive difficulties, promoting engagement in the writing process, and encouraging initiative in group discussions, educators can create an inclusive learning environment that fosters student’s ability to overcome anxiety barriers and excel in argumentative writing. However, it is important to acknowledge limitations in this research, including potential response bias due to self-report measures and the limited sample size from a specific educational institution, which may affect the generalizability of the findings. Future research should employ diverse assessment methods, and larger and more representative samples, and further explore the intricate connections between psychological, emotional, and cognitive symptoms of anxiety and their specific impacts on writing performance to enhance our understanding of this topic.